Visual Evoked Potentials and Effect of Relaxation Technique in Patients with Migraine: A Cross-Sectional Comparative Study - Biswas , Dalia A.; Gaikwad, Meghana A. (Current Overview on Disease and Health Research Vol. 1, 2022)
This is a cross-sectional comparative study wherein 15 cases of migraine (without aura) were compared to 1) group A 15 cases of migraine (without aura) on medicine alone, 2) group B 15 cases of migraine (without aura) who practiced Rajyoga meditation and deep breathing, and 15 age-matched normal people. This research was done during the interictal stage. The most remarkable observation was that group B had a drop in P100 (ms) at post-test in both eyes (albeit this was not significant), but group A had a substantial rise in P100 (ms) at post-test. Both the groups showed an increase in P100-N75 (\(μ v\)) & this finding was not significant in both For the right eye, multiple comparisons using the Tukey test and one way ANOVA revealed significant findings both between and within groups for P100 and N145 latencies. With the left eye, there was no discernible difference. We conclude that Rajyoga meditation and deep breathing can be used in conjunction with standard migraine treatment. We advocate for the continued use of these measures in order to reduce the frequency of assaults and, eventually, eliminate the problem.